Measuring the Development of Therapeutic-Decision-Making Skills by Practicing Pharmacists Undertaking a University-Based Postgraduate Clinical Qualification at Distance - Daniel F. B. Wright; Stephen B. Duffull; Kyle J. Wilby; Aynsley K. Peterson; Megan G. Anakin (MDPI AG, 2020)
(1) Background: The processes and skills required to make decisions about drug therapy have been termed "therapeutic decision-making" in pharmacy practice. The aim of this study was to evaluate a tool constructed to measure the development of therapeutic-decision-making skills by practicing pharmacists undertaking a university-based continuing professional development program. (2) Methods: A pre- and post-intervention crossover study design was used to investigate the qualitative and quantitative features of practicing pharmacists' responses to two clinical vignettes designed to measure the development of therapeutic-decision-making skills. The vignettes were assigned a score using a five-point scale and compared pre- and post-intervention. (3) Results: There was a median increase in score of 2 units on the five-point scale in the post-intervention scores compared to pre-intervention (p < 0.0001). (4) Conclusions: The results were interpreted to suggest that the participants' responses to the vignettes are a reasonable measure of student learning. Therefore, we infer that the teaching and learning intervention successfully enabled the development of therapeutic-decision-making skills by practicing pharmacists.